CARD3 Promotes Cerebral Ischemia‐Reperfusion Injury Via Activation of TAK1. Issue 9 (5th May 2020) - Wu, Xiaolin; Lin, Lijin; Qin, Juan‐Juan; Wang, Lifen; Wang, Hao; Zou, Yichun; Zhu, Xueyong; Hong, Ying; Zhang, Yan; Liu, Ye; Xin, Can; Xu, Shuangxiang; et al.
Abstract : Background: Although multiple signaling cascades and molecules contributing to the pathophysiological process have been studied, the treatments for stroke against present targets have not acquired significant clinical progress. Although CARD3 (caspase activation and recruitment domain 3) protein is an important factor involved in regulating immunity, inflammation, lipid metabolism, and apoptosis, its role in cerebral stroke is currently unknown. Methods and Results: Using a mouse model of ischemia‐reperfusion (I‐R) injury based on transient blockage of the middle cerebral artery, we have found that CARD3 expression is upregulated in a time‐dependent manner during I‐R injury. Further animal study revealed that, relative to control mice, CARD3‐knockout mice exhibited decreased inflammatory response and neuronal apoptosis, with reduced infarct volume and lower neuropathological scores. In contrast, neuron‐specific CARD3‐overexpressing transgenic (CARD3‐TG) mice exhibited increased I‐R induced injury compared with controls. Mechanistically, we also found that the activation of TAK1 (transforming growth factor‐β–activated kinase 1) was enhanced in CARD3‐TG mice. Furthermore, the increased inflammation and apoptosis seen in injured CARD3‐TG brains were reversed by intravenous administration of the TAK1 inhibitor 5Z‐7‐oxozeaenol. Conclusions: These results indicate that CARD3 promotes I‐R injury via activation of TAK1, which not only reveals a novel regulatory axis of I‐R induced brain injury but also provides a new potential therapeutic approach for I‐R injury.